The exchange contract in the Portuguese legal system and comparative law - Costa Machado, Sérgio Manuel Da (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Despite the exchange contract being one of the oldest contracts, it is not currently regulated in the Portuguese Civil Code, as it is understood that it belongs to a primitive state of the economy. The Portuguese legislator intended to make the purchase and sale contract the prototype of other onerous agreements according to article 939.º of the Civil Code. However, this will raise problems for us between the frontier of buying and selling and that of exchange, for which our law does not give us direct answers.We found that other legal systems, such as the Spanish, French, Italian, or Ibero-American codes, consecrate in their Civil Codes, in a brief way, the exchange contract.